The problem of succession to the Scottish throne and the English position on it 1286-1292 - Zahraa Riyad Nasser; Prof. Dr. Hassanein Abdel Kazem Ajja (Journal of College of Education, 2024)
Wars and conflicts often constituted a major aspect of the political relations that emerged between countries, and this matter became clear during the medieval period, which was filled with a huge collection of records of conflicts and wars between countries, some of which actively sought to impose hegemony and sovereignty over some other countries, especially Neighboring it, or sharing borders with it. Therefore, the conditions of the Scottish Kingdom begin with the death of the Scottish King Alexander III in 1286, then the death of the only heir to the Kingdom, his granddaughter Margaret of Norway in 1290, and the dispute that resulted from this over the Scottish throne and King Edward’s exploitation of this dispute. To interfere in the affairs of Scotland and impose his complete control over it, after placing obstacles to choosing a candidate for the Scottish Crown so that he would be an obedient tool in his hand until the appropriate time came for him to be the direct ruler of Scotland and make it subordinate to the English Crown. In general, the royal succession in Scotland constituted an important aspect of In the late Middle Ages, the throne crisis dominated the history of the succession to the crown of Scotland in the Middle Ages from 1286 to 1292. These events, in turn, led to bitter wars called the Wars of the Scottish Succession. King Edward I had a clear role in the crisis of the absence of an heir to the Scottish throne. , who made every effort to annex Scotland completely to England.